2016
DOI: 10.20517/2394-4722.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Do elderly NSCLC stage IV patients benefit from chemotherapy as well as younger? An analysis from clinical practice date

Abstract: How to cite this article: Gironés R, López P, Chulvi R, Cañabate M. Do elderly NSCLC stage IV patients benefit from chemotherapy as well as younger? An analysis from clinical practice date. J Cancer Metasta Treat 2016;2:379-87. Aim:The aim of this study was to evaluate the efficacy of treatment related to age in metastatic non-small cell lung cancer (NSCLC). We compared young and elders (> 70) in the setting of a regional Spanish hospital. We hypothesized that elder benefit as much as younger patients from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Despite the clear benefits in terms of survival, most of older patients with advanced NSCLC are undertreated or do not receive chemotherapy (Beckett et al, ; Davidoff, Tang, Seal, & Edelman, ). Nevertheless, it has been demonstrated that older patients can benefit from first‐line chemotherapy (Gironés, López, Chulvi, & Cañabate, ) despite displaying greater toxicity than younger patients receiving the same regimens (Meoni, Cecere, Lucherini, & Costanzo, ). The main criteria used to select patients for oncological treatments are ECOG performance status (PS) assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clear benefits in terms of survival, most of older patients with advanced NSCLC are undertreated or do not receive chemotherapy (Beckett et al, ; Davidoff, Tang, Seal, & Edelman, ). Nevertheless, it has been demonstrated that older patients can benefit from first‐line chemotherapy (Gironés, López, Chulvi, & Cañabate, ) despite displaying greater toxicity than younger patients receiving the same regimens (Meoni, Cecere, Lucherini, & Costanzo, ). The main criteria used to select patients for oncological treatments are ECOG performance status (PS) assessments.…”
Section: Introductionmentioning
confidence: 99%